Recent research progress on circular RNAs: Biogenesis, properties, functions, and therapeutic potential - Ashish Ranjan Sharma; Manojit Bhattacharya; Swarnav Bhakta; Abinit Saha; Sang-Soo Lee; Chiranjib Chakraborty (Elsevier, 2021)
Circular RNAs (circRNAs), an emerging family member of RNAs, have gained importance in research due to their new functional roles in cellular physiology and disease progression. circRNAs are usually available in a wide range of cells and have shown tissue-specific expression as well as developmental specific expression. circRNAs are characterized by structural stability, conservation, and high abundance in the cell. In this review, we discuss the different models of biogenesis. The properties of circRNAs such as localization, structure and conserved pattern, stability, and expression specificity are also been illustrated. Furthermore, we discuss the biological functions of circRNAs such as microRNA (miRNA) sponging, cell cycle regulation, cell-to-cell communication, transcription regulation, translational regulation, disease diagnosis, and therapeutic potential. Finally, we discuss the recent research progress and future perspective of circRNAs. This review provides an understanding of potential diagnostic markers and the therapeutic potential of circRNAs, which are emerging daily.